Die Bybel is steeds in diskussie: 'n dekade later - F. B. Doubell (Acta Theologica)
This article highlights the relationship between theology and context. In 1990 politics played a considerable role in South Africa. Authors such as F.E. Deist argued that one’s point of departure, whether theological or political, is crucial. In 1991 Deist wrote an article on the discussion of the Bible. He used three South African publications on Scripture to illustrate the ongoing discussion. The present article refers to Deist’s article on the discussion of the Bible in 1990 and then examines this discussion ten years later. It is concluded that the discussion on Scripture in 1990 differs from that in the year 2000. According to Deist, opposing theologians had to realise that the Bible is both a divine and a human book. This is accepted today, but some theologians go further and argue that the Bible is merely another human book. In 1990 criticism was divided between those who overemphasized the divine aspect and those who emphasized both the divine and the human aspects. Today criticism is divided between those who accept both the divine and the human aspects of Scripture and those who reject them. Ten years ago a political point of departure was acceptable within the overemphasized political context. Today there are theological and political differences in opinion.